IL-4 and IL-5 Secretions Predominate in the Airways of Wistar Rats Exposed to Toluene Diisocyanate Vapor - Kouame Kouadio; Kui-Cheng Zheng; Abdoulaye Abba Toure; Mireille Dosso; Hidemi Todoriki (Korean Society for Preventive Medicine, 2014)
ObjectivesWe established a Wistar rat model of asthma caused by toluene diisocyanate (TDI) exposure, and investigated the relationship between TDI exposure concentrations and respiratory hypersensitivity, airway inflammation, and cytokine secretions in animals, to better understand the mechanism of TDI induced occupational asthma.MethodsWistar rats were exposed to two different concentrations of TDI vapor four hours a day for five consecutive days. Bronchoalveolar lavage (BAL) was performed, and differential leucocytes from the BAL fluid were analyzed. Lung histopathological examination was carried out to investigate the inflammatory status in the airways. Production of cytokines interleukin (IL)-4 and IL-5 productions in the BAL fluid in vivo was determined with enzyme-linked immunosorbent assay kits.ResultsThe TDI-exposed rats exhibited greater airway hypersensitivity symptoms than the control rats. The BAL differential cell count and lung histopathological examination demonstrated that inflammation reactions were present in both the central and peripheral airways, characterized with marked infiltration of eosinophils in the TDI-exposed rats. The cytokine assay showed that IL-4 and IL-5 were predominantly produced in the BAL fluid in vivo.ConclusionsThese findings imply that TDI exposure concentrations may greatly affect the occurrence and extent of inflammatory events and that Th2 type cytokines may play an important role in the immunopathogenesis of TDI-induced occupational respiratory hypersensitivity.